2020
DOI: 10.1016/j.celrep.2020.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Pyruvate Kinase M2 Promotes Lung Cancer Metastasis through Activating the Integrin Beta1/FAK Signaling Pathway

Abstract: Graphical Abstract Highlights d Secreted PKM2 is a potential serum biomarker for diagnosing lung cancer d Secreted PKM2 promotes lung cancer progression d Integrin b1 functions as a receptor for secreted PKM2 d Targeting secreted PKM2 and integrin b1 can attenuate lung cancer metastasis SUMMARYCancer cell-derived secretomes have been documented to play critical roles in cancer progression. Intriguingly, alternative extracellular roles of intracellular proteins are involved in various steps of tumor progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 90 publications
3
55
0
Order By: Relevance
“…Lewis lung carcinoma originated from a spontaneous lung adenocarcinoma of a C57BL/6 mouse 32,33 . Tail vein injection of carcinoma cells was a classical method to establish models of metastasis 34‐36 . We injected the Lewis lung carcinoma cells (LLCs) into tail veins of six C57BL/6 mice, resulting in two lung metastases and three bone metastases.…”
Section: Resultsmentioning
confidence: 99%
“…Lewis lung carcinoma originated from a spontaneous lung adenocarcinoma of a C57BL/6 mouse 32,33 . Tail vein injection of carcinoma cells was a classical method to establish models of metastasis 34‐36 . We injected the Lewis lung carcinoma cells (LLCs) into tail veins of six C57BL/6 mice, resulting in two lung metastases and three bone metastases.…”
Section: Resultsmentioning
confidence: 99%
“…Further insights into the metabolic and non-metabolic roles of PKM2, and apparently discrepant functions, have been highlighted in several reports (e.g. Iqbal et al 2014;Amim et al 2019;Zahra et al 2020;Wang et al 2020a;Pascale et al 2020).…”
Section: The Warburg Effect: Essential Part Of Metabolic Reprogramminmentioning
confidence: 94%
“…The expression of PKM2 was found to be enhanced in two different strains of hepatocellular carcinoma cell lines by using 2D gel electrophoresis followed by MALDI-TOF mass spectrometry (64). Immunohistological staining of blood taken from patients with colon cancer (12) and gastrointestinal (65), pancreatic, lung (66), ovarian (67), and renal cell carcinoma (RCC) (68) showed that PKM2 is released into the blood circulation. Several studies demonstrated that the expression of PKM2 is up-regulated in colorectal cancer patients (CRC) and inflammatory bowel disease and intrahepatic cholangiocarcinoma (ICC) tissues with high tumor cell necrosis, high angiogenesis, and more advanced stages.…”
Section: Pkm2 As a Diagnostic Toolmentioning
confidence: 99%
“…Additionally, some PKM2 is also released into neighboring tissues by necrosis of cancer cells and tumor cell renewal, which can be used in the early diagnosis of cancer. The PKM2 level in the circulating blood of patients may serve as a potential diagnostic marker in various carcinomas (67).…”
Section: Pkm2 As a Diagnostic Toolmentioning
confidence: 99%